Suction/Injection Effects on the Swirling Flow of a Reiner-Rivlin Fluid near a Rough Surface. (5th January 2015) - Sahoo, Bikash; Poncet, Sébastien; Labropulu, Fotini
Abstract : The similarity equations for the Bödewadt flow of a non-Newtonian Reiner-Rivlin fluid, subject to uniform suction/injection, are solved numerically. The conventional no-slip boundary conditions are replaced by corresponding partial slip boundary conditions, owing to the roughness of the infinite stationary disk. The combined effects of surface slip (λ ), suction/injection velocity (W ), and cross-viscous parameter (L ) on the momentum boundary layer are studied in detail. It is interesting to find that suction dominates the oscillations in the velocity profiles and decreases the boundary layer thickness significantly. On the other hand, injection has opposite effects on the velocity profiles and the boundary layer thickness.